PENGARUH DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT TUNAS BARU LAMPUNG, TBK (Studi Kasus Di PT Tunas Baru Lampung,Tbk – PKS 4 Cinta Manis Lama, Banyuasin) - Muhammad Deni; Kemas Welly Angga Permana (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2021)
The research was conducted with the aim of knowing the extent of the influence of work discipline on the work productivity of employees of PT Tunas Baru Lampung, Tbk. The sample used in this study were employees of PT Tunas Baru Lampung, Tbk as many as 65 respondents, data and research information obtained from questionnaires/questionnaires. The approach method used by the researcher is a quantitative approach. Meanwhile, for data analysis using simple linear regression analysis and hypothesis testing using the T test. In this case the researcher manages the data calculations with the SPSS for windows 25 program. The results of testing the hypothesis show that the work discipline variable has a positive and significant effect on work productivity. Where from the results of the analysis obtained a simple linear equation as follows Y = 11.096 + 0.414 X , with the value of the correlation coefficient (R) obtained at 0.723 this shows that there is a positive direction of influence between work discipline on work productivity and the value of the coefficient of determination (Rsquer) is obtained. ) in this study of 0.522 where every 1% increase in the work discipline variable has an effect of 52.2% on employee work productivity and the rest is influenced by other factors not examined in this study. Then the results of the t test obtained the value of t_count > t_table (8.297 > 1.67) with a significant value of less than 0.05 (0.00 < 0.05) meaning that the hypothesis shows that Ho is rejected and Ha is accepted. So it can be concluded that the research hypothesis shows a positive and significant influence between work discipline variables on the work productivity of PT Tunas Baru Lampung, Tbk - PKS 4 Cinta Manis Lama employees.